E-Government Interoperability in Promoting E-Governance: A Study of the Super Mantab Application in Musi Rawas Regency - Erowati, Dewi; Farhan, Eva Kurnia; Astuti, Puji; Rizqi, Muhammad Dimas (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2026)
This study aims to analyze how e-government interoperability contributes to promoting effective e-governance through a case study of the Super Mantab Application implementation in Musi Rawas Regency, Indonesia. Interoperability in this context refers to the capability of various government systems and institutions to exchange, integrate, and utilize data, information, and public services seamlessly. The research employs a qualitative descriptive approach with a single-case study design. Primary data were collected through in-depth interviews with officials from the Department of Communication and Informatics, technical staff, and application users, while secondary data were obtained from policy documents and literature related to the Electronic-Based Government System (SPBE). Data were analyzed using NVivo 12 Plus software through coding, matrix coding query, and project map techniques to identify relationships among actors and key implementation factors. The findings reveal that the level of interoperability among government institutions in Musi Rawas Regency remains at an early stage, with limited data integration and institutional coordination. The most dominant factors influencing implementation success are communication effectiveness and the disposition of policy implementers, whereas bureaucratic structure and resource capacity remain the main challenges. Other obstacles include low public digital literacy, uneven network infrastructure, and regional regulations that are not yet aligned with national SPBE policies. Nevertheless, the Super Mantab Application has contributed to expanding access to digital public services and promoting local MSMEs. The study concludes that the success of interoperability depends not only on technological readiness but also on interagency coordination, leadership commitment, and citizen participation. Therefore, strengthening human resource capacity, promoting adaptive bureaucratic reform, and establishing regional policies that standardize interoperability are essential strategies to accelerate the transformation toward transparent, participatory, and sustainable e-governance.